Valerie Kincade Oppenheimer, The Female Labor Force in the United States : Demographic and Economic Factors Governing its Growth and Changing Composition, Population Monograph Series no. 5, Institute of International Studies, Berkeley, University of California, 1970. xii, 197 p. - Weiss-Altaner, Eric R. (Estudios Demográficos y Urbanos, 1975)
VALERIE KINCADE OPPENHEIMER, The female Labor Force in the United States: Demographic and Economic Factors Governing its Growth and Changing Composition, Population Monograph Series No. 5 Institute of International Studies, Berkeley, University of California, 1970.